Corruption and assortative matching of partners in international trade - Arusha Cooray; Chandan Kumar Jha; Bibhudutta Panda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
While the effects of corruption on bilateral trade have been relatively well explored, its effect on the composition of trading partners has not been studied. In this paper, we argue that corruption in a country is likely to impose asymmetric costs on its trading partners depending on their characteristics. As a result, as the level of corruption in a country changes, its trade flows from some of its trading partners change more than others depending on the latter's characteristics, causing a change in the composition of its trading partners. We focus on two characteristics of trading partners: the level of corruption and membership in the Organisation for Economic Cooperation and Development Convention on Combating Bribery of Foreign Public Officials in International Business Transactions. Using the gravity model, we find evidence of negative assortative matching in international trade with respect to corruption: that corruption in a country is negatively associated with trade flows from highly corrupt countries and positively associated with trade flows from signatories to the Convention. Our main results also confirm the findings of previous studies that both origin and destination country corruption discourage bilateral trade.
Keywords: D73; F14; K20; 330; corruption; international bribery; international trade; OECD Convention